Waardevolle Afrikaans genealogiese inligting. Voortrekkerstamouers 1835-1845 , Jan C. Visagie : book review (Historia, 2021)
At the outset I must declare my personal interest: I believe that Gandhi was one of the greatest historical figures – one of the very few personages whose shining example as an activist places him in (in my opinion) the company of Buddha, Jesus and Mohammed – although both his aims and results were of a humbler, more earthly nature. Therefore I was thrilled to receive EricItzkin’s little book. It opened the way for me to follow the South African path of Gandhi before he became the Mahatma. Itzkin skilfully interweaves historical fact, anecdote and physical location to create a vivid picture of the young Gandhi and his disciples.The result is a popular and readable book, based on reasonably extensive research that will be of special interest to Ghandi enthusiasts and everyone